2015
DOI: 10.1159/000365814
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Best Formula to Predict the Fetal Weight: Comparison of 18 Formulas

Abstract: Background: To compare the accuracy of 18 formulas in predicting fetal weight and also to make a comparison of these formulas in low-birth-weight fetuses (<2,500 g) and in fetuses weighing >4,000 g. Methods: Four-hundred-and-ninety-five pregnant patients were enrolled. The estimated fetal weight was calculated using 18 different formulas. The mean percentage error, the mean absolute percentage error and reliability analysis were used to compare the performance of the formulas. Results: The Cronbach's alpha was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 24 publications
0
28
4
Order By: Relevance
“…(17) Additionally, at earlier gestational ages, small changes in measurements can result in large changes in growth percentiles. (9) Given the relative lack of clinical data in this context, clinicians may wonder if growth restriction at the time of ultrasound to assess fetal anatomy without an identifiable cause represents true pathology or measurement imprecision.…”
Section: Discussionmentioning
confidence: 99%
“…(17) Additionally, at earlier gestational ages, small changes in measurements can result in large changes in growth percentiles. (9) Given the relative lack of clinical data in this context, clinicians may wonder if growth restriction at the time of ultrasound to assess fetal anatomy without an identifiable cause represents true pathology or measurement imprecision.…”
Section: Discussionmentioning
confidence: 99%
“…Studies describing new models have often reported that their model was superior to previously published ones, but this is an inevitable consequence of deriving and testing a model in the same population. In general, previous studies assessing the accuracy of different models for EFW in the prediction of birth weight have reached the conclusion that either the most, or among the most, accurate models were those reported by Hadlock et al 15 in all pregnancies, including those with a small or large baby [50][51][52][53][54][55][56][57] .…”
Section: Comparison With Previous Studiesmentioning
confidence: 93%
“…A Congolian study, the Singapore Chinese study and a UK study used the Hadlock formula involving AC, FL, BPD and HC (Hadlock (II)) instead [12,28,29]. Esinler et al compared different EFW algorithms and suggested that Hadlock (I) and Hadlock (II) had good and similar degree of accuracy [30]. Our study, the …”
Section: Comparison With Other Growth Standardsmentioning
confidence: 82%